Recovery of a Common Bean Landrace (Phaseolus vulgaris L.) for Commercial Purposes - Mallor, Cristina; Barberán, Miguel; Aibar, Joaquín (Frontiers in Plant Science, 2018)
The “Caparrona” bean is a landrace that was grown largely in Monzón, for what is also known by the name of “Caparrona de Monzón”. Historical references mention that in the thirties of the last century Caparrona beans reached a production higher than 200,000 kg. Nevertheless, the increasing industrialization of agriculture enhanced its replacement by modern varieties causing that only a few local growers continued producing Caparrona beans mainly for family auto-consumption. However, the high demand for local products, grown with environmentally-friendly farming techniques, has reawakened interest in this local bean. For recovering the Caparrona bean crop, a study was conducted with the aim to valorize such landrace, along all the process, from collecting seeds to securing the in situ and ex situ conservation. Six bean samples were initially collected from local farmers, and the traditional knowledge was also recorded. After the first seed borne virus control, two samples were rejected because the positive results for Bean Common Mosaic Virus (BCMV). The four remaining samples were evaluated in a randomized complete block design with three replications at two locations. Throughout the growing period, samples were taken for virus control. Two other samples resulted positive for BCMV and were discarded. Between the two healthy seed samples, regarding morphological, chemical composition and agronomic data, no significant statistical differences were found. Therefore, both samples were selected for commercial production. The obtained seeds from the assays were transferred to a recently created producers' association that registered a private label to commercialize the Caparrona beans as a gourmet product. Seeds are also available from the Spanish BGHZ-CITA public genebank